2019
DOI: 10.1002/1878-0261.12530
|View full text |Cite
|
Sign up to set email alerts
|

SGLT1 is required for the survival of triple‐negative breast cancer cells via potentiation of EGFR activity

Abstract: Sodium/glucose cotransporter 1 (SGLT1), an essential active glucose transport protein that helps maintain high intracellular glucose levels, was previously shown to interact with epidermal growth factor receptor (EGFR); the SGLT1–EGFR interaction maintains intracellular glucose levels to promote survival of cancer cells. Here, we explore the role of SGLT1 in triple‐negative breast cancer (TNBC), which is the most aggressive type of breast cancer. We performed TCGA analysis coupled to in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…FDG uptake in malignant tumors was mediated by Glucose transportase-1 (GLUT-1) 27 , Higashi et al 28 proposed the correlations between GLUT-1 expression and FDG uptake in NSCLC. EGFR, on the other hand, has a strong interaction with sodium/glucose cotransporter 1 (SGLT1) in various tumors 29 - 31 . As SGLT1 opposed to GLUT-1 27 , this mechanism may partly explaine less FDG avid in EGFR mutations.…”
Section: Discussionmentioning
confidence: 99%
“…FDG uptake in malignant tumors was mediated by Glucose transportase-1 (GLUT-1) 27 , Higashi et al 28 proposed the correlations between GLUT-1 expression and FDG uptake in NSCLC. EGFR, on the other hand, has a strong interaction with sodium/glucose cotransporter 1 (SGLT1) in various tumors 29 - 31 . As SGLT1 opposed to GLUT-1 27 , this mechanism may partly explaine less FDG avid in EGFR mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium/glucose co-transporter 1 (SGLT1) is essential for maintaining intracellular glucose concentration and can promote tumor growth by interacting with the epidermal growth factor receptor (EGFR) [ 86 ]. In vitro and in vivo analysis of SGTL1 transporter showed an important link between SGLT1-EGFR, regulating TNBC cell survival.…”
Section: Glycolytic Pathway Targeted By Classical Anticancer Drugsmentioning
confidence: 99%
“…In vitro and in vivo analysis of SGTL1 transporter showed an important link between SGLT1-EGFR, regulating TNBC cell survival. mRNA analysis of this transporter in BC tissue samples indicated the highest expression in TNBC and HER2+ than in luminal A or luminal B [ 86 ]. The same research group also showed that knockdown of SGLT1 significantly reduced TNBC proliferation and tumor size.…”
Section: Glycolytic Pathway Targeted By Classical Anticancer Drugsmentioning
confidence: 99%
“…After incubation with secondary goat anti-rabbit immunoglobulin conjugated to peroxidaselabelled dextran polymer (SV0002; Boster) at 37°C for 1 h, visualisation, counterstaining with haematoxylin and mounting were performed. Semi-quantitative evaluations of protein expression were scored on the basis of the intensity and the percentage of WDHD1-positive tumour cells as previously described [59][60][61][62] .…”
Section: Immunohistochemical and H/e Staining And Scoringmentioning
confidence: 99%